Role of echocardiography in acute stroke patients admitted to ICU - Lokesh SB; Latha V (Asian Journal of Medical Sciences, 2025)
Background: Stroke is gaining worldwide importance as the focus now shifts to non-communicable diseases. The etiological investigation of the potential cardiac source of acute ischemic stroke (AIS) is important for the secondary prevention of recurrent and future embolization and also helps in finding other etiology. Aims and Objectives: Our aim was to evaluate echocardiographic findings in patients with AIS admitted to a tertiary care hospital in ESICMC PGIMSR Rajajinagar. Materials and Methods: The prospective study was conducted on patients admitted in medical college hospitals affiliated to ESICMC PGIMSR Rajajinagar. All patients aged more than 18 years presenting with acute onset ischemic stroke were taken into the study. After demographic data transthoracic echocardiography was done and various finding was noted. Results: In our study, mean age was 56.07 years. Male was 55 (82.1%) and female were 12 (17.9%). In our study stroke in young i.e. <45 years is 10 patients (14.9%). Out of 67 patients, 31 had degenerative mital and aortic valvular, 7 had left atrial thrombus, 7 had left ventricular thrombus, mitral valve prolapse in 3 patients, regional wall motion abnormalities in 17 patients, heart failure with reduced ejection fraction in 21 patients, 4 patients had atrial septal defect, 2 patients had ventricular septal defect. Conclusion: This study reinforces the importance of transthoracic echocardiography in stroke. Transthoracic echocardiography is not only an effective tool in picking up the clots inside the cardiac chambers but also it was found to be significantly effective in detecting valvular lesions and small septal defects, such as patent foramen ovale.